Between Women’s Empowerment and Emancipation. - Magdalena Karolak (Arabian Humanities)
The aim of this article is to assess recent women empowerment reforms in Bahrain through the Foucauldian concept of governmentality. While the research reveals that women’s empowerment follows political and economic rationalities, official discourse is not devoid of contradictions. On the other hand, opposition movements have also shown a pragmatic approach to women’s participation in society. The article pinpoints the gap between empowerment and emancipation efforts by Bahraini women and, ultimately, point out opportunities triggered by the Arab Spring.